Accuracy of Rod Contouring to Desired Angles With and Without a Template: Implications for Achieving Desired Spinal Alignment and Outcomes. Issue 2 (March 2023) - Sardi, Juan Pablo; Ames, Christopher P.; Coffey, Skye; Good, Christopher; Dahl, Benny; Kraemer, Paul; Gum, Jeffrey; Devito, Dennis; Brayda-Bruno, Marco; Lee, Robert; Bell, Christopher P.; Bess, Shay; et al.
Study Design: Biomechanical Study. Objective: The search for optimal spinal alignment has led to the development of sophisticated formulas and software for preoperative planning. However, preoperative plans are not always appropriately executed since rod contouring during surgery is often subjective and estimated by the surgeon. We aimed to assess whether rods contoured to specific angles with a French rod bender using a template guide will be more accurate than rods contoured without a template. Methods: Ten experienced spine surgeons were requested to contour two 125 × 5.5 mm Ti64 rods to 40°, 60° and 80° without templates and then 2 more rods using 2D metallic templates with the same angles. Rod angles were then measured for accuracy and compared. Results: Average angles for rods bent without a template to 40°, 60° and 80° were 60.2°, 78.9° and 97.5°, respectively. Without a template, rods were overbent by a mean of 18.9°. When using templates of 40°, 60° and 80°, mean bend angles were 41.5°, 59.1° and 78.7°, respectively, with an average underbend of 0.2°. Differences between the template and non-template groups for each target angle were all significant (p < 0.001). Conclusions: Without the template, surgeons tend to overbend rods compared to the desired angle, while surgeons improved markedly with a template guide. This tendency to overbend could have significant impact on patient outcomes and risk of proximal junctional failure and warrants further research to better enable surgeons to more accurately execute preoperative alignment plans.